RELATIONSHIP BETWEEN SELF-ESTEEM AND TEST ANXIETY OF SECONDARY SCHOOL STUDENTS IN ECONOMICS IN UGHELLI, DELTA STATE (NAU Journal of Technology and Vocational Education, 2024)
The study was designed to determine the relationship between self-esteem and testanxiety of senior secondary school students in Economics in Ughelli, Delta State. Fiveresearch questions were raised and two hypotheses were formulated for the study. Thestudy adopted correlational-descriptive research design. The population of studycomprised 172 SS II Economics students from two private secondary schools inUghelli. A sample size of 60 SS II Economics students made up of (30 male and 30female Economics students) was selected for the study using convenient samplingtechnique. The researchers adapted Rosenberg Self-Esteem Scale (1965) and TestAnxiety Questionnaire (Suinn, 1969) as instruments for data collection. Cronbachalpha statistic was used to establish the reliability co-efficient of Rosenberg SelfEsteem Scale which yielded 0.76 while that of Test Anxiety Questionnaire was 0.81.Mean and standard deviation were used to answer research question 1 and 2 whilePearson Product Moment Correlation Coefficient was used to answer researchquestion 3, 4 and 5 and in testing the hypotheses at 0.05 level of significance.Findings of the study revealed that private secondary schools male Economicsstudents have high self-esteem score than their female counterparts. The study furtherdisclosed that private secondary schools female Economics students have high testanxiety score than their male counterparts. In addition, the study revealed that anegative and low relationship exists between self-esteem and test anxiety of privatesenior secondary school students in Economics irrespective of their gender. More so,outcome of the study indicated that a significant relationship exists between male andfemale students’ self-esteem and their test anxiety in Economics and the nullhypotheses were rejected. The researchers concluded that high self-perception tend toreduces students’ level of anxiety in Economics in private secondary schools. Thestudy recommended among others that, female secondary schools students’ shoulddevelop positive attitude and see Economics subject as an interesting subject.
Keywords: Secondary school education, Economics, self-esteem and test anxiety.